A COMPREHENSIVE EXAMINATION OF POST-MORTEM SPERM RETRIEVAL TECHNIQUES– A REVIEW ARTICLE (Journal of Forensic Medicine & Toxicology, 2024)
Post-mortem sperm retrieval (PMSR) has emerged as a promising option for women desiring to conceive a child after the demise of their partner. This procedure involves the collection of sperm from deceased individuals, primarily males, to facilitate assisted reproductive techniques. The retrieval process, typically performed surgically or via electroejaculation, aims to obtain viable sperm shortly after death. Subsequently, the collected sperm can be cryopreserved for future use in in vitro fertilization (IVF) or intrauterine insemination (IUI). While PMSR presents an avenue for women to realize their dreams of parenthood with their departed partners, it is essential to recognize the ethical complexities and legal variations surrounding its application. Consent and the rights of the deceased are crucial considerations in this emotionally charged domain. Furthermore, the optimal retrieval technique remains elusive, hindering the successful procurement of an adequate sperm sample. In this comprehensive review, we present an overview analysis of various techniques involved in post-mortem sperm retrieval, as well as an examination of current techniques employed for retrieval and preservation.
Keywords: Post Mortem Sperm Retrieval; Techniques; Assisted Reproduction; Cryopreservation